PENGANGGURAN DAN INFLASI SEBAGAI SEBUAH HUBUNGAN TERBALIK ATAU HUBUNGAN POSITIF - Agustono Agustono (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2005)
This article explores the relationship between unemployment an inflation. Applying a regression analysis approach to the study the relationship between unemployment and inflation. Conclution of this study, as (1) the relationship between unemployment and inflation is positif and (2) coeffesien of regression in 1,64